Original articleInvolvement of D2/D2 dopamine antagonists upon open-arms exploratory behaviours induced by intra-nucleus accumbens shell administration of N-methyl-D-aspartate - Razavi, Samira; Haeri-Rohani, Ali; Eidi, Akram; Zarrindast, Mohammad R. (Folia Neuropathologica, 2014)
Glutamatergic system stimulation in some parts of the brain may affect anxiety-related behaviours, aversive learning and memory. This system retains many interactions with dopaminergic neurotransmission. We have studied the effect of nucleus accumbens (NAc) shell glutamatergic system activation on anxiety-related behaviours as well as aversive learning and memory in adult male Wistar rats using the N-methyl-D-aspartate (NMDA) receptor agonist, NMDA. Furthermore, the possible involvement of the NAc shell dopamine D 2 and D 2 receptors upon NMDA-induced effects was evaluated. The elevated plus-maze task was used to assess the drugs’ concomitant effects on anxiety, learning and memory in rats. All drugs were delivered into the NAc shell via bilaterally implanted indwelling cannulae. The NMDA-induced anxiolytic-like behaviours upon retest could possibly be attributed to the further avoidance acquisition impairments. Moreover, the inhibition of dopaminergic system using SCH 23390 and sulpiride induced an anxiolytic-like response and impaired the aversive memory acquisition during retest. However, the concurrent intra-NAc shell microinjection of the subthreshold dose of SCH 23390 and sulpiride (0.125 µg/rat) reversed the anxiolytic-like effect and blocked the aversive memory impairment induced by intra-NAc shell NMDA. Our results suggest a modulatory role of the NAc shell dopaminergic system on NMDA-induced effects in the aversive memory.